Revelando as essências da educação maker: percepções das teorias e das práticas - Soster, Tatiana Sansone (2018)
This research aims to unveil the elements of Maker Education and whether they promote the emancipatory education, through theory and practices analysis. It also seeks to contribute for the knowledge production in this new domain that still lacks studies and publications for its theoretical reference, especially in Portuguese. The research is inspired on the Phenomenological approach by proposing investigative procedures that allow the theoretical elements to emerge and unveil the elements of practice. As a result of this research, it can be observed that the theoretical proposal and the practical realization of Maker Education are merging in many elements, having few distinct characteristics and many complementary ones. The theoretical characteristics of the Critical Pedagogy element have not been observed in practice. In fact, there was only the proposal of critical reflection on the students learning process in the pedagogical proposals of project documentation. Theoretical elements such as Constructionism and Constructivism have not been identified on the practices. However, the majority of the characteristics emerged as a practice of Maker Education. The curriculum in both theory and practice is associated with the knowledge areas of STEM & STEAM, and maker skills, systemically excluding all Humanities fields but Arts, at least on the projects hereby analyzed. It can be said that Maker Education is under construction and, therefore, still presents learning pedagogical results beneath from its theory, especially in regards to individuals critical development and integration of Maker practices into all areas of knowledge via the curriculum. The limited vision in applying Maker Education to STEM/STEAM and for developing student autonomy only on the school activities context have limited its potential. It can be verified on the research the undeniable power of Maker Education in producing mobilizing conditions for methodologies, practices, teaching and learning experiences in digital and physical technologies environments within the formal education context, ensuring access to Information and Communication Technologies (ICT) and computational thinking. In order to help building an overview of the analyzed practices, a summarizing chart containing the elements of Maker Education is presented, being constructed from the analysis, discussion and follow up of the theory and practices observed